Phonological System of Tengger Dialect : In Ngoko Speech Level - Dwi Astuti Wahyu Nurhayati (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
This research reports on Phonological System of Tengger Dialect (in Ngoko Speech Level) and focuses on how the consonant, vowel system, the syllabic, cluster construction are; what factors influence Phonological System Tengger Dialect in Ngoko Speech Level. Techniques of collecting data include field observations, recordings and direct interviews. The analysis includes reducing data, presenting the data, conclusion. Notes and phonetic transcription are classified into lingual unit, and they are written into version of ordinary words and form of symbols. Patterns of Tengger syllabic construction are: cvcvcv-kawula, cvc-nak, cvcvc-paran, cccvcvvc-nggate’en, cvccv cekne, cv cvcvcvc -ta baliken, cvvcc-reang, different phonemic happens in suffix na ® en,” Ta balikna ta baliken, nggatekna-nggate’en (from syllabic na en),jare ® njare (embedded sound n before j). Different lexicon also happens in sesuk-kesuk-tomorrow, ora ana-nana –nothing.The factors contributing to the survival of the dialect are that the speakers live in remote and isolated area such as forest.